Nonglycosylated mouse L cell interferon produced by the action of tunicamycin. - Jun–ichi Fujisawa; Yoichiro Iwakura; Yoshimi Kawade (1978)
The effect of tunicamycin, a specific inhibitor of protein glycosylation, on interferon production by L cells induced by Newcastle disease virus was studied. The interferon yields in the presence of tunicamycin ranged from 20 to 100% of control in various experiments. The two molecular species of normal L cell interferon with 40,000 and 24,000 daltons were completely eliminated, and a new species of a smaller size (18,000 daltons) was produced. Radiolabeling of interferon with [35S]methionine and [3H]glucosamine added to the induced cultures, as studied by immunoprecipitation and polyacrylamide gel electrophoresis, indicated that the two species of control interferon were both glycoproteins but tunicamycin interferon contained little or no sugar. In support of this was the loss of binding to lectin from Wistaria floribunda. A change in physical property of the molecule due to the absence of sugar was found in decreased heat stability in the presence of sodium dodecyl sulfate, although in its absence no significant difference from control interferon was observed. These results indicate that tunicamycin is an effective agent in producing nonglycosylated but fully active interferon molecules; the sugar moiety appears to be unnecessary for the antiviral activity and for secretion from cells.